A Quantitative Framework to Evaluate the Seismic Resilience of Hospital Systems - Shang, Qingxue; Wang, Tao; Li, Jichao (Journal of earthquake engineering : JEE, 2022)
A framework to quantitatively evaluate seismic resilience of hospital systems is proposed. A typical hospital system is categorized and importance factors for different functional units, subsystems, and components are quantified. Resilience demand is expressed as desirable recovery time of hospital system after earthquakes. Seismic resilience is quantiﬁed based on probabilistic seismic fragility analysis. Recovery time is calculated considering an idealized repair path. Loss of functionality of the hospital is evaluated as sum of weighted economic losses of all components. Case study of a hospital building was performed to demonstrate the feasibility and effectiveness of the proposed framework.